Perancangan WEB-GIS Penyebaran Wabah Penyakit Demam Berdarah Dengue (DBD) dan Malaria di Kota Bandar Lampung - Kurnia Muludi; Anie Rose Irawati; Anggun Falianingrum (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
Dengue Fever (DBD) and Malaria are kinds of diseases that often caused an extraordinary occurrence in Indonesia. Both diseases can spread rapidly and cause death in short time. The prediction of occurrence of Dengue Fever (DBD) and Malaria diseases in Bandar Lampung, still processed manually and presented in form of tables and graphs. In this research, Web-based Geographic Information System (WEB-GIS) was developed to provide information of the spreading of Dengue Fever (DBD) and Malaria diseases in the City of Bandar Lampung. Data was obtained from the Department of Health of the City government. The WEB-GIS was implemented using Arcview, MapServer, MySQL database, and PHPMapscript programming language. The result shows that WEB-GIS could provide information of spreading area of Dengue Fever (DBD) and Malaria diseases in Bandar Lampung until village level.Keywords : Dengue Fever, Malaria, WEB-GIS